How the Use of Renewable Energy Influences the Quality of the Natural Environment: The Case of Poland - Frodyma, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The use of different energy sources is an increasingly serious challenge for the countries for which sustainable development also means better use of energy resources and environmental improvement. The production and use of energy influences our living standards, but at the same time degrades and destroys  the environment. The main aim of the study is to assess the impactthe energy sources used have on the natural environment in Poland. The paper discusses changes in how energy is acquired from traditional and renewable sources in individual provinces in Poland.It  also analyses the state of the natural environment, with particular reference to air and water pollution. An attempt is made to assess whether increasing the use of renewable energy sources has a positive impact on reducing environmental degradation.